Xuechao Song - Identification of Polyamide 6 and Polyamide 66 Oligomers Using Ion Mobility Time-of-flight Mass Spectrometry and Their Migration from Kitchenware to Foodstuff - Song, Xuechao (Jornada de Jóvenes Investigadores del I3A, 2020)
Póster presentado en la IX Jornada de Jóvenes Investigadores del I3A